PENGARUH STORE ATMOSPHERE, KUALITAS PELAYANAN, DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA TOKO FASHION DEWA AYU SHOP KLUNGKUNG - Ni Kadek Dwi Yuliani; Ni Wayan Eka Mitariani; Ni Putu Cempaka Dharmadewi Atmaja (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2021)
Purchasing decisions are things that must be considered by consumers in the process of fulfilling the needs of a product or service. Every company must expect a high purchasing decision on its products or services such as Dewaayushop Klungkung fashion store. The purchasing decision making process in each person is basically the same, there are several factors that influence purchasing decisions, among others, store atmosphere, quality of service and price perception. This research was conducted in Dewaayushop Klungkung fashion store, taking samples used by as many as 80 respondents As for the sample technique used by the author in conducting this research using non probability sampling technique that is by accidental sampling approach, namely sampling technique based on coincidence. The collected data is analyzed with multiple linear regressions. Data collection using observations, interviews and questionnaires. Data is processed by using, Isntrumen Test, Classic Assumption Test, Multiple Linear Regression Analysis, Multiple Correlation Analysis, Determination Coefficient Test (R2), F-(F-test), Partial Test (T Test). The results showed that store atmosphere, service quality and price perception. positive and significant effect on the purchasing decision at Dewaayushop Klungkung fashion store. Further research can develop this research using other variables in theory have an influence on purchasing decisions